Enhancing Quranic and fardhu ain programmes through hybrid learning among orphans at Rumah Amal Baitul Kasih, Rawang - Sahrir, Muhammad Sabri; Mat Daud, Nuraihan; Ahmed Mahmoud, Ahmed Ragheb; Ahmad H.Osman, Rahmah; Zubir, Badri Najib; Nawi, Amani; Adzif, Azlilah; Ismail, Nur Shuhadak (Knowledge Transfer Programme, Ministry of Higher Education, Malaysia, 2016)
This project involves the transfer of knowledge between a university community and an orphanage. The project applies the hybrid learning method which is a combination of the traditional and computerassisted approaches to enhance the Quranic Recital, Fardhu Ain and Arabic language programs. This KTP project is combining the theories of multimedia learning by Mayer (2001) and hybrid learning by Nicole & Retta (2006) in the activities. Mayer (2001) states that " people learn more deeply from words and pictures than from words alone", while Nicole & Retta (2006) mentioned that the hybrid learning approch is effective in carrying out 'in-depth learning'. An orphanage was chosen as the partner for this project because the orphans are in dire need of attention and support. The project helps to ensure that they are not left behind. The researchers chose to teach Quranic recital and Fardhu Ain since the skills could help to make them a better person. The religious and moral values which are embedded in these two courses may help towards producing ethical manpower in the future. This paper presents some of activities that were held in the first quarter of 2014. It was successfully run with a few modifications to the strategies and timing of the activities. Some of the children were found to be extremely weak in their Jawi script writing skill and Arabic language proficiency. Hence more time was needed to assist them during the the learning activities. This project implies the need for the government to set up a special care center for orphans under its supervision which integrates education and welfare in ensuring a brighter future for this needy group.